Complementary substrate specificity and distinct quaternary assembly of the Escherichia coli aerobic and anaerobic β-oxidation trifunctional enzyme complexes. Issue 13 (15th July 2019) - Sah-Teli, Shiv K.; Hynönen, Mikko J.; Schmitz, Werner; Geraets, James A.; Seitsonen, Jani; Pedersen, Jan Skov; Butcher, Sarah J.; Wierenga, Rik K.; Venkatesan, Rajaram
Abstract : The trifunctional enzyme (TFE) catalyzes the last three steps of the fatty acid β-oxidation cycle. Two TFEs are present in Escherichia coli, EcTFE and anEcTFE. EcTFE is expressed only under aerobic conditions, whereas anEcTFE is expressed also under anaerobic conditions, with nitrate or fumarate as the ultimate electron acceptor. The anEcTFE subunits have higher sequence identity with the human mitochondrial TFE (HsTFE) than with the soluble EcTFE. Like HsTFE, here it is found that anEcTFE is a membrane-bound complex. Systematic enzyme kinetic studies show that anEcTFE has a preference for medium- and long-chain enoyl-CoAs, similar to HsTFE, whereas EcTFE prefers short chain enoyl-CoA substrates. The biophysical characterization of anEcTFE and EcTFE shows that EcTFE is heterotetrameric, whereas anEcTFE is purified as a complex of two heterotetrameric units, like HsTFE. The tetrameric assembly of anEcTFE resembles the HsTFE tetramer, although the arrangement of the two anEcTFE tetramers in the octamer is different from the HsTFE octamer. These studies demonstrate that EcTFE and anEcTFE have complementary substrate specificities, allowing for complete degradation of long-chain enoyl-CoAs under aerobic conditions. The new data agree with the notion that anEcTFE and HsTFE are evolutionary closely related, whereas EcTFE belongs to a separate subfamily.